The global decline of the mandatory death penalty : constitutional jurisprudence and legislative reform in Africa, Asia, and the Caribbean /: constitutional jurisprudence and legislative reform in Africa, Asia, and the Caribbean. (2016) - Novak, Andrew
No abstract available